Efectividad agronómica y económica de la fertilización líquida y granulada en el cultivo de maní (Arachis hypogaea L.) bajo condiciones de secano en Tosagua - Solorzano Panta, María Elizabeth (2023)
The aim of the research was to evaluate the agronomic and economic effectiveness of liquid and granulated fertilization in peanut cultivation under rainfed conditions. The aim of the research was to evaluate the agronomic and economic effectiveness of liquid and granulated fertilization in peanut cultivation under rainfed conditions. The experiment was carried out in El Viento Community in Tosagua canton, Manabí. The treatments evaluated were: injected liquid fertilization (T1), liquid fertilization in superficial drench (T2), granulated fertilization in superficial band (T3), granulated fertilization buried (T4), control treatments (T5). The main variables recorded were grain yield (GY), NPK agronomic efficiency (AENPK) and economic profitability (EP). The GY and AENPK were significantly influenced (p<0.05) by the fertilization treatments evaluated. The highest GY was reached with the T1 and T2 treatments, which achieved a yield of 2105.50 and 2002.12 kg/ha-1. Likewise, the highest AENPK was achieved with the T1 and T2 treatments. In the same way, these same treatments (T1 and T2) reached the highest EP with 86 and 76%, respectively, which indicates that for each dollar invested there was a return of 0.80 and 0.76 dollars. It is concluded that, under rainfed conditions, in the Tosagua area, it is more convenient and profitable to carry out injected liquid fertilization and superficial drenching.